2003
DOI: 10.1046/j.1365-2788.2003.00517.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk markers associated with challenging behaviours in people with intellectual disabilities: a meta‐analytic study

Abstract: A meta-analysis of prevalence and cohort studies conducted over the last  years was carried out to identify risk markers for challenging behaviour shown by individuals with intellectual disabilities (IDs). A total of  potential studies was identified from the review, with  (  .  %) containing sufficient data to enable a statistical analysis to be conducted. Results indicated that males were significantly more likely to show aggression than females, and that individuals with a severe/profound degree of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

42
426
7
9

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 588 publications
(484 citation statements)
references
References 31 publications
(25 reference statements)
42
426
7
9
Order By: Relevance
“…This meta-analysis construed that it was extremely arduous to make comparisons between studies to formulate a median prevalence of aggression against others due to the variances of methodologically studies. However, McClintock et al (2003) did find that males were significantly more likely to show aggression against others than females, as this study did.…”
Section: Discussionsupporting
confidence: 58%
“…This meta-analysis construed that it was extremely arduous to make comparisons between studies to formulate a median prevalence of aggression against others due to the variances of methodologically studies. However, McClintock et al (2003) did find that males were significantly more likely to show aggression against others than females, as this study did.…”
Section: Discussionsupporting
confidence: 58%
“…The study also noted a significant decline in maladaptive behaviors over the eight-year study period for most groups, including those with autism. A meta-analysis of research on maladaptive behaviors in children and adults with different types of intellectual disabilities found that aggression, disruptive behavior, and selfinjury were significantly more prevalent among those with ASD than other types of intellectual disabilities (McClintock, Hall, & Oliver, 2003). However, a recent study of 487 school children with pervasive developmental disorders (Lecavalier, 2005) found the least prevalent maladaptive behaviors were selfinjury and physical aggression.…”
Section: Prevalence and Change In Maladaptive Behaviors In Adolescencmentioning
confidence: 99%
“…Due to the number of different genetic syndromes employed in the study, participants were not comparable on a number of risk markers known to impact on the development of repetitive behavior including: level of ability, mobility, verbal ability, vision and hearing (Ando & Yoshimura, 1978;Fazzi et al, 1999;Guess, 1966;McClintock, 2003;Vitiello et al, 1989). Due to the non-parametric nature of the Repetitive Behaviour Questionnaire data, these differences could not be taken into account at a statistical level.…”
Section: Association With Autism Spectrum Phenomenologymentioning
confidence: 99%